Relationship Between Perception of Service Quality and Students’ Satisfaction – A Case Study of a Management School - Baniya, Rojan (Journal of Education and Research, 2016)
This study examines the relationship between service quality dimensions (SERVQUAL Model) and overall service quality and satisfaction of management students. Additionally, this study identifies critical factors amongst service quality dimensions that contribute most to students’ satisfaction. Furthermore, this study examines whether the relationship between overall service quality and student satisfaction is valid at both Bachelor in Business Administration (BBA) level and Master in Business Administration (MBA) level. Self-administered online surveys were conducted among the undergraduate and graduate students of a management school in Kathmandu to collect the data, which were analysed using correlations and regressions. Both ‘dimensions of service quality’ and ‘composite service quality construct’ had positive relationship with students’ satisfaction, such that at both graduate and undergraduate level, service quality is antecedent of students’ satisfaction. Among the dimensions of service quality, empathy and responsiveness were found to be significant predictors of service quality. The empirical results of this study attest to Parasuraman, Zeithaml, and Berry’s (1985) SERVQUAL. This study also provides a basis for further validation of relationship between service quality and student satisfaction in future. Finally, it suggests management schools to improve their service quality, and its various dimensions, leading to students’ satisfaction.